2009
DOI: 10.1111/j.1349-7006.2008.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy of oxaliplatin and 5‐fluorouracil may be an effective regimen for mucinous adenocarcinoma of the ovary: A potential treatment strategy

Abstract: Resistance of ovarian mucinous adenocarcinoma to standard chemotherapy with paclitaxel and carboplatin is associated with poor prognosis, and an effective treatment is needed. The present study aimed to identify an effective chemotherapy for ovarian mucinous adenocarcinoma. Five human ovarian mucinous adenocarcinoma cell lines (MN-1, OMC-1, RMUG-L, RMUG-S, TU-OM-1) were used in this study. Sensitivity of the cells to the anticancer agents was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 30 publications
2
38
0
3
Order By: Relevance
“…The authors concluded that NACT-IDS appears to increase the risk for platinum resistance [55]. Drug resistance after NACT correlates with in vitro drug resistance [56][57][58][59]. A second possible explanation for why NACT-IDS has not been able to further improve OS might be the violation of the dose-density effect by the interruption of chemotherapy with IDS [60].…”
Section: Nact-ids Versus No Surgerymentioning
confidence: 99%
“…The authors concluded that NACT-IDS appears to increase the risk for platinum resistance [55]. Drug resistance after NACT correlates with in vitro drug resistance [56][57][58][59]. A second possible explanation for why NACT-IDS has not been able to further improve OS might be the violation of the dose-density effect by the interruption of chemotherapy with IDS [60].…”
Section: Nact-ids Versus No Surgerymentioning
confidence: 99%
“…17 Preclinical data have suggested a synergism of oxaliplatin and 5-fluorouracil in cisplatin-resistant experimental models. 18 This synergism results from down-regulation of the excision-repair cross-complementation group 1 by 5-fluorouracil, resulting in enhanced sensitivity to oxaliplatin. Furthermore, irinotecan, another effective agent in gastrointestinal malignancies, has been used in small series for the treatment of these tumors with encouraging results.…”
mentioning
confidence: 99%
“…The 5 MAC cell lines used in this study (RMUG-L, RMUG-S, MN-1, OMC-1 and MCAS) (21)(22)(23)(24)(25) , 100 U/ml penicillin, and 100 µg/ml streptomycin (Gibco) at 37˚C in a 5% CO 2 atmosphere for no longer than 8 weeks after recovery from frozen stocks.…”
Section: Methodsmentioning
confidence: 99%